Long term direct injection diesel engine operation on vegetable oil/diesel blends - Tippayawong N. (2014)
Vegetable oils are a potential alternative to the partial or total substitution of diesel fuels. It was known that short-term engine tests have been successful with vegetable oils, however, long-term tests have revealed the fuel's limitations regarding lubricating oil contamination, deposits on engine surfaces and injection problems. In this ongoing research study, properties of palm oils and diesel blends were determined and long-term engine tests of palm oils and diesel blends were performed on a modern direct injection diesel engine at a speed of 2500 rev/min under part load condition for almost 250 hours. Results of engine torques, specific fuel consumptions, black smoke emissions and injection pump surface inspection were compared between diesel and palm oil/diesel blends. Engine performance, smoke emissions and fuel consumption were found to change slightly with running time. Surface wear and accumulations of metal debris in crankcase lube oil samples were found to increase with time, but not in an unusual rate. Wear was not significantly different in the test engine fueled with diesel or palm oil/diesel blend. Results for palm oil/diesel blends were comparable to those for diesel. An overall evaluation of results indicated that the palm oil/diesel blends can be substituted for diesel fuel in engine operation. Copyright © 2003 Society of Automotive Engineers of Japan, Inc.